Immunogenicity and Safety of a Booster Dose of Live Attenuated Varicella Vaccine, and Immune Persistence of a Primary Dose for Children Aged 2 to 6 Years - Yukai Zhang; Lei Wang; Yanxia Wang; Wei Zhang; Ningning Jia; Zhiqiang Xie; Lili Huang; Wangyang You; Weifeng Lu; Erwei Li; Feilong Gao; Yuansheng Hu; et al. (Vaccines, 2022)
Aim: To evaluate the immunogenicity and safety of a booster dose of live attenuated varicella vaccine (VarV) manufactured by Sinovac (Dalian) Vaccine Technology Co. Ltd., and the immune persistence of a primary dose in 2- to 6-year-old children. Methods: A phase IV, open-label study was conducted in China. Children previously vaccinated with a single dose of VarV at 1~3 years old received one dose of homologous VarV in the first year, the second year, or the third year after the primary immunization as booster immunization. Immune persistence was evaluated in an immune persistence analysis set, while immunogenicity was evaluated in a per-protocol analysis set, and safety was evaluated in a safety analysis set. The primary endpoint was the seropositive rate and the seroconversion rate of VarV antibody. The trial was registered at ClinicalTrials.gov (NCT02981836). Results: From July 2018 to August 2020, a total of 849 vaccinated children received the booster vaccination of VarV, one booster dose for each child (301 vaccinated in the first year after primary immunization (Group 1), 276 vaccinated in the second year after primary immunization (Group 2), 272 vaccinated in the third year after primary immunization (Group 3)). The seropositive rates were 99.34%, 97.83%, and 98.16% in Groups 1–3, with GMTs of 1:22.56, 1:18.49, and 1:18.45, respectively. Thirty days after the vaccine booster dose, the seropositive rates of the three groups were all 100% and the seroconversion rates were 52.54%, 67.46%, and 66.67%, with GMTs of 1:68.49, 1:76.32 and 1:78.34, respectively. The seroconversion rates in Groups 2 and 3 were both higher than that in Group 1 (p = 0.0005 and p = 0.0008). The overall incidence of adverse reactions was 7.77%, with 7.64%, 8.33%, and 7.35% in Groups 1, 2, and 3, respectively. The main symptom among adverse reactions was fever, the incidence of which ranged from 5.07% to 6.64% in each group, and no vaccine-related serious adverse events occurred. Conclusions: VarV had good immune persistence in 1~3 years after primary immunization. A vaccine booster dose for children aged 1~3 years after primary immunization recalled specific immune response to varicella-zoster virus, with no safety concerns increased.